Google Tour Builder: Tracking the Impact of Civil War Veterans in a Kansas Community. Issue 2 (4th March 2021) - Scheuerell, Scott
Abstract: The author describes how high school students can use Google Tour Builder to track the impact of local Civil War veterans by conducting research with primary and secondary sources. In the article, there is a description of an example from Larned, Kansas where more than one hundred Civil War veterans settled a community on the plains. Digitized primary sources from the Kansas State Historical Society can be accessed on the Internet to investigate how the veterans were among the earliest settlers of the community and many served in key government positions. The activity presented can be replicated by teachers elsewhere to enable students to participate in local history research. Census reports, plat maps, and rosters from the Grand Army of the Republic enable students to research and produce an interactive Google Tour Builder. The site can enable the rest of the community to learn about the impact of veterans who lived there. Today students can enter the name of any Civil War veteran into an Internet database sponsored by the National Park Service. Students can use the database to mine for information such as where the soldier enlisted, location of battles fought, and how many soldiers died in the regiment.